Moment curvature of reinforced concrete beams in ordinary grade embedded with bacteria (Bacillus subtilis) - Reddy, S. Sunil Pratap; Murthy, N.R.D.; Rao, M.V. Seshagiri; Sasikala, Ch. (Journal of Structural Engineering, 2025)
The objective of the present investigation is to obtain the moment curvature of reinforced concrete beams by the microbiologically induced special growth/filler. An attempt is made by using the bacteria Bacillus subtilis strain no.JC3 for the study of moment curvature relationship in reinforced concrete beams. Calcite formation by Bacillus subtilis JC3 is a model laboratory bacterium, which can produce calcite which precipitates on suitable media supplemented with a calcium source. The equations of the stress-stain curve for concrete in ordinary grade (M20) are used to study the Moment-Curvature characteristics of bacterial concrete beam sections. The theoretical procedure has been validated by conducting an experimental investigation on beams. The experimental values have shown good correlation with the analytical values of moments and curvatures.